Lipid profile improvement after four group psychological interventions in combination to nutritional and physical activity instructing among overweight and obese individuals. - Mojgan Agah Heris; Ahmad Alipour; Masoud Janbozorgi; Reza Hajihosseini; Farhad Shaghaghi; Neda Golchin; Shahnaz Nouhi (Tehran University of Medical Sciences, 2013)
Research background approved weight loss would result in improvement of lipid profile. Nowadays, weight management is attained by modifying psychological mediators, as well as dieting and making individuals do more physical activity. Hence, This research was performed to compare effectiveness of different psychological interventions on lipid profile improvement among individuals with overweight and obesity.Using quasi-experimental design, 68 participants with mean age 26 years and 9 months (ranged from 20 to 43) were randomly assigned into 4 groups (including LEARN, CBT, CT, and MCT), and eventually 61 participants completed the treatment protocols. BMI was calculated by Omron digital body composition instrument, and blood lipids and glucose concentrations were measured prior to and after all interventions.Data analysis by using t-test for dependent groups analysis revealed lipid profile, FBS, and BMI were significantly modified after applying 4 interventions comparing baseline and post treatment mean differences(P